ETHICAL CONSIDERATIONS IN ADAPTIVE SELLING - Jain, Neha; Nim, Dheeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Adaptive selling, the exercise of modifying sales tactics to specific customer requirements and circumstances, has verified to augment sales performance and customer satisfaction. However, this approach advances significant ethical considerations that can affect faith, long-standing customer associations, and the wider insight of the sales job. The paper discovers the ethical scopes of adaptive selling, concentrating on matters such as manipulation, transparency, respect and equity for customer independence. It inspects the stability between influential methods and ethical duty, stressing on probable menaces such as abusing client susceptibilities or distorting data to close agreements. Through an evaluation of current literature and real-world case studies, the study delivers understandings to sales experts steering these ethical dilemmas. It offers practical procedures for upholding veracity while enhancing sales tactics, safeguarding adaptive vending nurtures belief and sustainable associations in progressively active marketplace.